2012
DOI: 10.1073/pnas.1206840109
|View full text |Cite
|
Sign up to set email alerts
|

In vitro loading of human cohesin on DNA by the human Scc2-Scc4 loader complex

Abstract: The loading of cohesin onto chromatin requires the heterodimeric complex sister chromatid cohesion (Scc)2 and Scc4 (Scc2/4), which is highly conserved in all species. Here, we describe the purification of the human (h)-Scc2/4 and show that it interacts with hcohesin and the heterodimeric Smc1-Smc3 complex but not with the Smc1 or Smc3 subunit alone. We demonstrate that both h-Scc2/4 and h-cohesin are loaded onto dsDNA containing the prereplication complex (pre-RC) generated in vitro by Xenopus high-speed solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 31 publications
6
50
1
Order By: Relevance
“…Vertebrate Scc2 and Scc4 orthologs interact physically through their amino termini (10,13,17,18), but budding yeast Scc2 appears to lack the corresponding amino-terminal region. Nevertheless, we found that Scc2 cleavage prevents its coimmunoprecipitation with Scc4, indicating that the budding yeast Scc2 amino-terminal domain is required for stable interactions with Scc4.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Vertebrate Scc2 and Scc4 orthologs interact physically through their amino termini (10,13,17,18), but budding yeast Scc2 appears to lack the corresponding amino-terminal region. Nevertheless, we found that Scc2 cleavage prevents its coimmunoprecipitation with Scc4, indicating that the budding yeast Scc2 amino-terminal domain is required for stable interactions with Scc4.…”
Section: Discussionmentioning
confidence: 99%
“…The amino termini of human and Xenopus Scc2 homologs are required for interactions with their respective Scc4 orthologs (10,13,17,18). Whether this requirement is true in budding yeast is unclear, however, because S. cerevisiae Scc2 lacks the corresponding amino-terminal region present in multicellular eukaryotic homologs.…”
Section: Scc2 Cleavage Eliminates Its Interactions With Scc4 and Redumentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence indicating an involvement of the pre-RC in the cohesin recruitment to the chromatin has been obtained for other organisms as well. In vitro experiments in X. laevis showed that an extract containing pre-RC provides interaction between the human cohesin complex and DNA, and this interaction may be blocked by inhibitors of the pre-RC assembly [76]. ChIP-seq analysis in D. melanogaster showed that the majority of ORC binding sites coincides with the sites of cohesin localization, thus supporting evidence for the involvement of pre-RC in cohesin recruitment to DNA [77].…”
Section: Sister Chromatid Cohesionmentioning
confidence: 99%